1996
DOI: 10.1021/jp960002z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependences of Singlet Methylene Removal Rates

Abstract: The technique of laser flash photolysis/laser absorption has been used to obtain absolute removal rate constants for singlet methylene, 1 CH 2 (a ˜1A 1 ), in the temperature range 298-462 K. The temperature dependences of the removal rate constants for N 2 , CH 4 , C 2 H 4 , C 2 H 6 , H 2 O, H 2 CO, CH 2 CO, CH 3 F, C 2 F 6 , and CH 3 OH were measured and the Arrhenius parameters determined. For the reacting species, CH 4 , C 2 H 4 , C 2 H 6 , H 2 O, H 2 CO, CH 2 CO, CH 3 F, and CH 3 OH, the rate constants exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…For comparison, Table 3 shows literature values of kinetic data for removal of 1 CH 2 as well as the isoelectronic species NH( 1 ∆) with several collision partners. [31][32][33][34][35] As shown, Xe is a faster relaxer of NH( 1 ∆) than N 2 by more than 2 orders H + CH 2 CO f products (6) 3 CH 2 + CH 2 CO f products (7) of magnitude. This is presumably due to the well-known heavy atom effect in promoting spin-forbidden processes.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, Table 3 shows literature values of kinetic data for removal of 1 CH 2 as well as the isoelectronic species NH( 1 ∆) with several collision partners. [31][32][33][34][35] As shown, Xe is a faster relaxer of NH( 1 ∆) than N 2 by more than 2 orders H + CH 2 CO f products (6) 3 CH 2 + CH 2 CO f products (7) of magnitude. This is presumably due to the well-known heavy atom effect in promoting spin-forbidden processes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in flames indicated that the presence of water has an important thermal effect, reducing the flame temperature because of the heat capacity of water [19]. Since as the temperature decreases, the formation of soot is limited, and the addition of water should result in a decrease of soot formation.…”
Section: Watermentioning
confidence: 99%
“…However, there have been measurements of the temperature dependence of 1 CH 2 +Ar, He, and N 2 [4,10,11], for which the CIISC yield is unity. The rate coefficients all increase with temperature; for example, for 1 CH 2 + Ar k CIISC increases from 5 to 15 · 10 À12 cm 3 molecule À1 s À1 between 295 and 860 K [4].…”
Section: Introductionmentioning
confidence: 99%